Kontroversi Seputar Naskh Al-Quran - Hamid, M. Abdul (el Harakah: Jurnal Budaya Islam, 1999)
Naskh which is an urgent and principal problem, has a wide and high complication in Islamic theology and fiqh. There are at least two types of naskh accepted by the majority of Muslim jurists, namely Alhukm wa Attilawah (the abolition of law and recitations) and naskh al hukm duna al tilawah (abolition of the law but no text). Knowledge of the naskh and manssukh is one of the urgent things to understand the Quran as part of the ulumu of the Qur'an. The clerical controversy surrounding the Quranic verse, the question of naskh - mansukh may remain a controversial issue. However, he should not reduce faith to the characteristics of the Qur'an that should be positioned proportionally by everyone who claims to believe in the Qur'an. For instance one should not reduce Mujadalab and shahadab to actualize its values in all things. Indeed, the Koran is not enough just to be a moral foundation. Naskh yang merupakan masalah yang urgen dan pokok, memiliki komplikasi yang luas dan tinggi dalam teologi dan fikih Islam. Paling tidak ada dua jenis naskh yang diterima oleh mayoritas ahli hukum muslim, yaitu naskh Alhukm wa Attilawah (penghapusan hukum maupun tilawah) dan naskh al hukm duna al tilawah (penghapusan hukum tetapi tidak ada teksnya). Pengetahuan tentang naskh dan manssukh adalah salah satu hal yang urgen untuk memahami al Quran sebagai bagian dari ulumu al Quran. Kontroversi ulama seputar naskb al Quran, persoalan naskh - mansukh boleh jadi tetap sebagai persoalan kontroversal. Tetapi, ia tidak boleh mengurangi keimanan kepada karakteristik al Quran yang harus diposisikan secara proporsonal oleh setiap orang yang mengaku mengimani al Quran. Sebagai contoh tidak bolehnya mengurangi Mujadalab dan syahadab untuk mengaktualisasikan nilai-nilainya dalam segala hal. Memang al Quran tidak cukup hanya dijadikan landasan moral.